Cultural adaptation of Quality Of Care Through The Patient's Eyes -QUOTE-HIV - Tiago Cristiano de Lima; Maria Isabel Pedreira de Freitas
ABSTRACT Objective: to translate and adapt Quality of Care Through the Patient's Eyes - HIV (QUOTE-HIV) for the Brazilian population living with HIV/AIDS. Method: a methodological study, which followed the stages of translation, synthesis, back-translation, evaluation by the committee of experts and pre-test for cultural adaptation of the instrument. Results: the process of translation and cultural adaptation was considered adequate. Evaluation by the expert committee resulted in semantic, structural and grammatical adequacy of the evaluated items. 30 subjects considered the instrument to be easy to understand and suggested minor adjustments in some items. Conclusion: the Brazilian version of QUOTE-HIV has been adapted and validated in relation to its content. However, this is a study that precedes the process of evaluating the psychometric properties of the instrument, the results of which will be presented in a later publication.